Wild Animal Movement Detection and Alert System - Mrs A Praveena,; M. Sai Maruthi Kalyan,; M. Basha Sayed,; N.V.S. Nikhil,; P Likithsrikanth, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The “Wild Animal Movement Detection and Alert System” repr esents an innovative approach to wildlife monitoring, leveraging advancements in artificial intelligence and embedded systems to track and analyze animal activity in their natural habitats. This project integrates the ESP32CAM, a low cost yet highly efficie nt micro controller with image capturing capabilities, with the YOLO (You Only Look Once) object detection algorithm, which i s renowned for its real time, high accuracy classification and loc alization of objects. The ESP32CAM serves as the primary vide o capturing device, continuously streaming live footage that is p rocessed through YOLO to detect the presence of wild animals. Upon detecting wildlife activity, the system generates alerts that are instantaneously communicated to designated users via a mo bile application or webbased interface. These alerts provide criti cal, realtime updates, enabling researchers, conservationists, and relevant stakeholders to monitor wildlife movements and respo nd promptly to potential threats or opportunities for intervention. The primary goal of this system is to enhance wildlife monitorin g and conservation efforts by introducing an intelligent, automat ed mechanism to observe animal behavior, assess movement pat terns, and gather actionable data. One notable advantage of this solution is its ability to mitigate human wildlife conflicts, partic ularly in areas where proximity to human settlements poses risks to both humans and animals. By providing early warnings about the presence of wildlife near human habitats or agricultural area s, this system empowers communities to adopt preventative mea sures, safeguarding lives and livelihoods while protecting wild s pecies from harm. Furthermore, the system’s capacity to track a nimal activities over time allows researchers to gain deeper insig hts into biodiversity, migration patterns, and habitat utilization. Such data is vital for informed decisionmaking in conservation p lanning and ecological research. Methodologically, the system is built on the foundation of cuttin gedge technologies tailored to deliver accuracy and efficiency in challenging, resourcelimited environments. The YOLO algorith m, known for its ability to detect multiple objects in a single fra me with high speed, ensures the timely identification and classif ication of a wide range of animal species. The compact and pow erefficient ESP32CAM further enhances the portability and scal ability of the project, enabling deployments even in remote or ru gged locations. The system’s integration with mobile and webba sed platforms ensures a seamless user experience, granting stake holders easy access to notifications, analysis, and realtime monit oring data. By utilizing a combination of hardware and software solutions, the project strikes a balance between affordability and functionality, making it suitable for deployment in diverse ecol ogical contexts. The significance of the “Wild Animal Movement Detection and Alert System” lies in its multifaceted impact on biodiversity con servation and wildlife management. Traditional methods of wild life monitoring, often reliant on manual observation or static ca meras, are laborintensive, inefficient, and prone to human error. This project addresses these limitations by offering an automate d, scalable solution capable of functioning continuously without the need for constant human intervention. Additionally, it bridge s the gap between technology and conservation, demonstrating h ow artificial intelligence can be harnessed to address some of th e most pressing challenges in the natural world. Beyond conserv ation, the system also has implications for public safety and agri cultural protection, making it a versatile tool with widespread ap plications. By promoting coexistence between humans and wildl ife and contributing to sustainable conservation practices, this pr oject underscores the transformative potential of technology in p reserving the planet’s biodiversity.